Analýza rozvoje malé obchodní firmy - Čechová, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce se zabývá hodnocením finanční a ekonomické situace společnosti prostřednictvím vybraných metod finanční analýzy. Obsahuje návody, postupy a potřebné informace ke zvýšení prosperity firmy.

The Bachelor's Thesis deals with the evaluation of financial and economic situation of the company through selected methods of financial analysis. This includes instructions, procedures and informations needed to increase the prosperity of the company.
Small Trade Company Development Analysis
Keywords: Finanční analýza; zisk; manažerské účetnictví; přidaná hodnota; výrobní proces; Financial Analysis; Profit; Management Accounting; Value Added; Manufacturing Process